Determinants of dyslipidaemia in probands with polycystic ovary syndrome and their sisters - Joharatnam, Jalini (Clin Endocrinol (Oxf), 2011)
OBJECTIVE: Polycystic ovary syndrome (PCOS) is associated with dyslipidaemia and obesity. It is not clear whether the dyslipidaemia of PCOS is attributable to PCOS itself, obesity, or a combination of both. Our objective was to assess the importance of familial dyslipidaemia in PCOS by comparing fasting lipids between probands and their (affected and nonaffected) sisters. DESIGN: Retrospective data set analyses. PATIENTS: Family study; 157 probands, 214 sisters and 76 control women (normal ovaries and regular cycles). All probands had PCOS, defined by symptoms of anovulation and/or hyperandrogenism with polycystic ovaries on ultrasound. Affected or unaffected status of sisters was defined by ovarian morphology. MEASUREMENTS: Serum concentrations of triglycerides, total cholesterol, high-density lipoprotein (HDL)-cholesterol and low-density lipoprotein (LDL)-cholesterol. RESULTS: Triglyceride levels and body mass index (BMI) were higher and HDL cholesterol levels were lower in the probands than affected sisters, unaffected sisters and controls. These differences in lipid profiles between the groups disappeared after adjustment for BMI. No differences in lipids were seen between affected and unaffected sisters. CONCLUSIONS: These data are consistent with heritability of lipid levels in sisters but strongly suggest that the predominant influence on the manifestation of dyslipidaemia in PCOS is body weight.